Ultra-fine CuO Nanoparticles Embedded in Three-dimensional Graphene Network Nano-structure for High-performance Flexible Supercapacitors. (20th April 2017) - Li, Yanrong; Wang, Xue; Yang, Qi; Javed, Muhammad Sufyan; Liu, Qipeng; Xu, Weina; Hu, Chenguo; Wei, Dapeng
Abstract: High conductivity, large specific surface area and excellent performance redox materials are urgently desired for improving electrochemical energy storage. However, with single redox material it is hard to achieve these properties. Herein, we develop ultra-fine CuO nanoparticles embedded in three-dimensional graphene network grown on carbon cloth (CuO/3DGN/CC) to construct a novel electrode material with advantages of high conductivity, large specific area and excellent redox activity for supercapacitor application. The CuO/3DGN/CC with different CuO mass ratios are utilized to fabricate supercapacitors and the optimized mass loading achieves the high areal capacitance of 2787 mF cm −2 and specific capacitance of 1539.8 F g −1 at current density of 6 mA cm −2 with good stability. In addition, a high-flexible solid-state symmetric supercapacitor is also fabricated by using this CuO/3DGN/CC composite. The device shows excellent electrochemical performance even at various bending angles indicating a promising application for wearable electronic devices, and two devices with area 2 × 4 cm 2 in series can light nine light emitting diodes for more than 3 minutes.